1977
DOI: 10.1038/269304a0
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a dinucleoside phosphate–drug complex as model for nucleic acid–drug interaction

Abstract: The crystal structure of a 3:2 complex of the frameshift mutagen proflavine with the dinucleoside phosphate cytidylyl-3'5'-guanosine has been determined. The complex has one drug molecule intercalated between Watson--Crick base pairs of the nucleotide duplex. The other two proflavine molecules are bound to the exterior of the miniature double helix. The orientation of the base pairs in this miniature double helix has aspects similar to that found in RNA 11.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0
1

Year Published

1979
1979
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(34 citation statements)
references
References 26 publications
1
32
0
1
Order By: Relevance
“…Instead of having unwinding associated with the bases surrounding the intercalator, there is unwinding associated with the base pair one removed from the intercalator. A 00 unwinding angle has already been observed in the r(CpG)-proflavin complex (6). The total amount of unwinding seen per daunomycin is 80, compared with 26°observed with ethidium (5).…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…Instead of having unwinding associated with the bases surrounding the intercalator, there is unwinding associated with the base pair one removed from the intercalator. A 00 unwinding angle has already been observed in the r(CpG)-proflavin complex (6). The total amount of unwinding seen per daunomycin is 80, compared with 26°observed with ethidium (5).…”
Section: Resultsmentioning
confidence: 81%
“…Up to the present, only structures of dinucleoside phosphates associated with intercalators have been determined (4)(5)(6)(7)(8). These generally yielded an unwinding angle but provided no information about perturbations farther away.…”
Section: Resultsmentioning
confidence: 99%
“…According to this principle, every second (next-neighbor) intercalation site along the length of the DNA double helix remains unoccupied. Experimental evidence for this principle has been found in fiber diffraction studies on nucleic acid fibers bound to metallointercalative agents (2,3), in single-crystal studies (4)(5)(6)(7)(8) on complexes between dinucleoside monophosphates complexed with intercalating drugs, and solution studies on binding of ethidium ion to oligonucleotides of ribose and deoxyribose sugars (9). Based on earlier crystallographic studies (4-6) that suggested mixed sugar puckering at the intercalation site, a stereochemical basis for the neighbor-exclusion principle was proposed.…”
mentioning
confidence: 99%
“…Based on earlier crystallographic studies (4-6) that suggested mixed sugar puckering at the intercalation site, a stereochemical basis for the neighbor-exclusion principle was proposed. However, this mixed sugar puckering scheme has not been shown to be essential for creating intercalating sites in double-helical DNA through several crystal structure and model building studies (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…It may be of interest that a recent study (Neidle, Achari, Berman, Glusker and Stalling 1977) has shown that both proflavine and ethionine bind to the DNA molecule, being inserted into the double helix.…”
Section: "Nodules" (Table 2)mentioning
confidence: 99%